EFFECTIVE PERFORMANCE MANAGEMENT SYSTEM FOR ENHANCING GROWTH AT ACCRA TECHNICAL UNIVERSITY - Hervie, Dolores Mensah (Archives of Business Research, 2018)
Performance management supports and offers a structure for employees to develop the skills they need to achieve organisation’s strategic goals. The key features of PMS involve setting objectives, monitoring, motivation, giving timely feedback and measurable performance. There are regular day-to-day meetings as well as periodic feedback meetings with subordinates. An unbiased annual evaluation of performance based on specific assessable targets set at the beginning of the corporate year is carried out. During these end-of-year appraisal face-to-face meetings, achievements and non-achievements of targets are discussed objectively. Necessary steps are then taken to either recognize or improve performance, enhance career development, promote, reward and compensate as deemed fit. The objective of this study is to propose the introduction of Performance Management System in Accra Technical University that would enhance performance and effective growth. A semi structured questionnaire was used and interviews were conducted to gather information from a cross-section of staff in the institution. In all, about 30 questionnaires were distributed and retrieved from both senior and administrative junior staff. PMS manual was designed based on information gathered. The manual spells out the step-by-step procedure or guideline for a successful implementation of PMS. The study concludes and recommends among other things that efforts should be made by the Institution to ensure that staff are given the requisite training in the area of target setting and implementation, recognition of employees’ effort and enhance career development which would go a long way to achieve institutional strategic goals and competitive advantage for Accra Technical University